A qualitative study of the allergy testing experiences, views and preferences of adult patients. Issue 1 (December 2016) - Brown, Clare; Jones, Christina; Stuttaford, Laura; Robertson, Annalee; Rashid, Rabia; Smith, Helen
Abstract Background Patients can be tested for IgE sensitivities with in vivo or in vitro testing, but patients' experiences of different allergy test modalities have not been studied. The objective of this study was to investigate adult patients' experiences, views and preferences for allergy testing, exploring skin prick testing and allergen-specific IgE testing. Methods A qualitative study of adults attending out-patients for investigation of a suspected allergy. A purposive, convenience sample identified participants and semi-structured interviews were conducted, face to face or by telephone. Interviews were recorded and transcribed verbatim. Thematic content analysis was used to explore patients' experiences. Results 23 patients were interviewed. The characteristics of skin prick tests particularly valued were the immediacy and visibility of results, which enabled testing and interpretation to be achieved within a single clinic appointment. In vitro testing offered patients simplicity and procedural speed, necessitating only a single puncture site, and was perceived to be a superior test as it was conducted in a laboratory. Conclusions The patient preferred method of allergy testing was skin prick testing rather than in vitro allergen specific IgE testing. However, most patients were accepting of either testing modality because their desire to confirm or exclude an allergic trigger overrode any perceived disadvantages of the test method. Trial registration Not applicable as study descriptive and qualitative.